Covid-19 infection in children with cancer after the first wave in Turkey: A study of the Turkish pediatric oncology (TPOG) and hematology (TPHD) societies - Kebudi, R.; Kurucu, N.; Tuğcu, D.; Eker, N.; İnce, D.; Tokuç, G.; Çeçen, R. E.; Sevinir, B.; Vural, O.; Erdem, M.; Demirdağ, T.; Koç, A.; et al. (Wiley, 2021)
[Abstract Not Available]
Keywords: Covid-19; Turkish Pediatric Oncology; Hematology